2011
DOI: 10.1088/0964-1726/20/10/105011
|View full text |Cite
|
Sign up to set email alerts
|

Secure wireless actuation of an implanted microvalve for drug delivery applications

Abstract: The capability to wirelessly control fluid flow through a microvalve can emerge as an attractive technology enabling various biomedical applications such as remote drug delivery and in vitro diagnostics. Contactless powering of such a microvalve is best addressed by near-field inductive coupling due to its close proximity to the external interrogator. In this paper, we propose the use of the same technique for secure remote interrogation and powering of a human implantable, surface acoustic wave (SAW) correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The valve was designed to be driven by the minimum value about electromagnetic (EM) radiation, considering existing EM radiation. Length about the required code was researched to guarantee safe manipulation [122,123,125,126]. Zhang et al reported a novel SAW microvalve consisted of the piezoelectric substrate and an interdigital transducer (27.5 MHz).…”
Section: Metal Phase Transition Actuation Low Melting Point Alloymentioning
confidence: 99%
See 1 more Smart Citation
“…The valve was designed to be driven by the minimum value about electromagnetic (EM) radiation, considering existing EM radiation. Length about the required code was researched to guarantee safe manipulation [122,123,125,126]. Zhang et al reported a novel SAW microvalve consisted of the piezoelectric substrate and an interdigital transducer (27.5 MHz).…”
Section: Metal Phase Transition Actuation Low Melting Point Alloymentioning
confidence: 99%
“…There are lots of advantages in the realization of a SAW microvalve including secure [122], reliable and low power operation [121], small size [123], simplicity in construction [124] and cost effectiveness [125]. Such microvalves have a huge range of applications such as in micro electro-mechanical systems (MEMS), nano electro-mechanical systems (NEMS) [121], biomedical applications, lab-on-chip applications [124], drug delivery [125,126], and so on.…”
Section: Metal Phase Transition Actuation Low Melting Point Alloymentioning
confidence: 99%
“…Manshadi et al [31] Circular/inside a microchamber/DC 500 96.89% developed for basic fluid flow mechanistic studies [102], in vitro diagnostics [103], and biological sample delivery [104]. Rapid response and ability to be integrated into microfluidic systems are the essential criteria for selecting appropriate microvalves.…”
Section: Icek Microvalvesmentioning
confidence: 99%
“…Second, current methods have limitations in constructing entirely biocompatible medical devices. Microelectromechanical systems (MEMS) devices (2)(3)(4)(5) feature moving parts manufactured with methods developed for silicon and metals [such as thin-film deposition, photolithography, and etching (6)], but silicon-based materials present challenges as implantable devices because of their low biocompatibility (7)(8)(9). This limitation extends to implantable electronic devices that use silicon-based transistor circuits, which further require a reliable power supply via either a toxic battery or electronic interconnects between the interior and exterior of the body.…”
Section: Introductionmentioning
confidence: 99%